Maintaining the Independence of the International Criminal Court: The Legal and Procedural Implications of an Article 16 Deferral Request - Kim, Sum (2011)
The International Criminal Court (ICC) and the United Nations (UN) are independent international institutions with overlapping interests in the field of international peace and security. The ICC and the UN have a mutually cooperative yet independently functioning relationship, even though the ICC was originally conceived as a judicial body closely related to the UN and working in association with the UN Security Council. The interrelationship between the ICC and the Security Council was an issue of rigorous debate in the negotiation processes and preparatory commission of the ICC Statute. The travaux préparatoires of the ICC Statute show that the drafters acknowledged the primary role of the Security Council in determining threats or breaches of the peace and acts of aggression. This is reflected in the ICC Statute where the Security Council maintains two distinct powers in the functioning of the ICC. First, under Article 13(b) the Security Council may, acting under Chapter VII of the UN Charter, refer a situation to the ICC. The referral power of the Security Council is unique in that it allows the ICC to bypass the territory and nationality bases for jurisdiction required for a State party referral or the Prosecutor acting in proprio motu. Second, under Article 16 the Security Council may, acting under Chapter VII, request the ICC to defer a situation or prosecution for a period of twelve months, with the possibility of renewal.